2012
DOI: 10.1128/aem.00301-12
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase A 2 Inhibitors Synthesized by Two Entomopathogenic Bacteria, Xenorhabdus nematophila and Photorhabdus temperata subsp. temperata

Abstract: bThe entomopathogenic bacteria Xenorhabdus nematophila and Photorhabdus temperata subsp. temperata suppress insect immune responses by inhibiting the catalytic activity of phospholipase A 2 (PLA 2 ), which results in preventing biosynthesis of immune-mediating eicosanoids. This study identified PLA 2 inhibitors derived from culture broths of these two bacteria. Both X. nematophila and P. temperata subsp. temperata culture broths possessed significant PLA 2 -inhibitory activities. Fractionation of these bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 38 publications
(54 reference statements)
2
80
0
6
Order By: Relevance
“…Previous studies have shown that EPN infection of some insects results in rapid melanization and encapsulation of IJs although in permissive hosts IJs can escape the capsule and kill the insect (51)(52)(53). Both Xenorhabdus and Photorhabdus produce specific inhibitors of phospholipase A 2 , a key component of the melanization and encapsulation reactions, suggesting that the bacterial endosymbionts of EPNs promote nematode survival by suppressing these reactions (54,55). To test whether infection with S. carpocapsae-X.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that EPN infection of some insects results in rapid melanization and encapsulation of IJs although in permissive hosts IJs can escape the capsule and kill the insect (51)(52)(53). Both Xenorhabdus and Photorhabdus produce specific inhibitors of phospholipase A 2 , a key component of the melanization and encapsulation reactions, suggesting that the bacterial endosymbionts of EPNs promote nematode survival by suppressing these reactions (54,55). To test whether infection with S. carpocapsae-X.…”
Section: Resultsmentioning
confidence: 99%
“…Genome analysis of Photorhabdus spp. has revealed many genes responsible for the production of metabolites other than proteinous metabolites (Duchaud et al 2003;Park et al 2013), and biochemical analyses of culture extracts have confirmed the existence of secondary metabolites such as antimicrobial and insecticidal compounds (Seo et al 2012), siderophores (Watson et al 2005), and phytohormones indole-3-acetic acid . Photorhabdus spp.…”
Section: Introductionmentioning
confidence: 99%
“…and Pseudomonas sp. are active against variety of insects as well as against microbial pathogens of plants and animals (Seo et al, 2012). In the present study, the potent EPS producing Pseudomonas sp.…”
Section: Resultsmentioning
confidence: 89%